Power resources, territory and labour conflicts in the logistic sector: a relational perspective on the Mondo Convenienza struggle. - della Porta, Donatella; Antonelli, Marco (Social Movement Studies)
Based on an approach to power resources that links studies on social movements with those on labour sociology, in this article we examine the mobilizations that took place at Mondo Convenienza, a large Italian company involved in the logistic sector, against extreme forms of exploitation. We suggest that, in order to understand these forms of 'mobilisations against the odds', we need to consider a) multiple resources activated during the struggle, which go beyond the traditional focus on structural and associational resources; b) how these resources are used by networks which are built up during the mobilization, linking together different actors, including but not formed exclusively by traditional trade unions; c) how multiple strategies are developed, d) with the emergence of a broad framing. These resources must be seen as e) produced in the course of the protests. Our research points to the rooting of social resources in a territory characterized by a tradition of high associational density that is reactivated to support the mobilization of the workers. Our results show how power resources are influenced by the social and political context in which workers are embedded. Therefore, contextual factors – such as political legacies and the local context of mobilization – emerge as relevant for understanding variations in organizing practices. In this sense, we note that the social and non-institutional dynamics of the local environment in which workers are embedded are affected by a specific protest culture and related social networks that characterize a given location inside and outside the workplace.